An analysis of the mortality situation in Southern Transdanubia Region according to main groups of diseases - Molnárné Barna, Katalin; Molnár, Tamás (Acta Scientiarum Socialium, 2011)
An analysis of the mortality situation in Southern Transdanubia Region according to main groups of diseases A country’s economic performance is greatly influenced by the population’s health status because the number of healthy life years has a positive affect on the economy. This is the reason why European Union researches the relationship between health and the economy. Therefore, it is important to review and analyze the population’s health status in the regions. This paper shows the mortality situation in the Southern Transdanubia Region.